Numerical Investigation of Mixed Convection on a Stagnation Point Flow Past a Stretching Vertical Surface with Convective Boundary Conditions - M. K. A., Mohamed; Mohd Zuki, Salleh (2014)
In this study, the mathematical modeling for mixed convection on a stagnation point flow past a stretching vertical surface with convective boundary conditions is considered. The transformed boundary layer equations are solved numerically using the Keller-box method. The numerical solutions are obtained for the local heat transfer coefficient, the surface temperature as well as the velocity and the temperature profiles. The features of the flow and heat transfer characteristics for various values of the Prandtl number, stretching parameter, buoyancy parameter and conjugate parameter are analyzed and discussed.